Theory of legitimate expectations for public administration - Brown, Alexander 1974 December 27- (Oxford, United Kingdom : Oxford University Press, 2017)
It is an unfortunate but unavoidable feature of even well-ordered democratic societies that governmental administrative agencies often create legitimate expectations (procedural or substantive) on the part of non-governmental agents (individual citizens, groups, businesses, organizations, institutions, and instrumentalities) but find themselves unable to fulfil those expectations for reasons of justice, the public interest, severe financial constraints, and sometimes harsh political realities. How governmental administrative agencies, operating on behalf of society, handle the creation and frustration of legitimate expectations implicates a whole host of values that we have reason to care about, including under non-ideal conditions-not least justice, fairness, autonomy, the rule of law, responsible uses of power, credible commitments, reliance interests, security of expectations, stability, democracy, parliamentary supremacy, and legitimate authority. This book develops a new theory of legitimate expectations for public administration drawing on normative arguments from political and legal theory. Brown begins by offering a new account of the legitimacy of legitimate expectations. He argues that it is the very responsibility of governmental administrative agencies for creating expectations that ought to ground legitimacy, as opposed to the justice or the legitimate authority of those agencies and expectations. He also clarifies some of the main ways in which agencies can be responsible for creating expectations. Moreover, he argues that governmental administrative agencies should be held liable for losses they directly cause by creating and then frustrating legitimate expectations on the part of non-governmental agents and, if liable, have an obligation to make adequate compensation payments in respect of those losses. --
Includes bibliographical references and index.
Keywords: Public administration; Public administration